2000
DOI: 10.4049/jimmunol.165.4.1896
|View full text |Cite
|
Sign up to set email alerts
|

αβTCR+ Cells Are a Minimal Fraction of Peripheral CD8+ Pool in MHC Class I-Deficient Mice

Abstract: MHC class I molecules play a role in the maintenance of the naive peripheral CD8+ T cell pool. The mechanisms of the peripheral maintenance and the life span of residual CD8+ cells present in the periphery of β2-microglobulin-deficient (β2m−/−) mice are unknown. We here show that very few CD8+ cells in β2m−/− mice coexpress CD8β, a marker of the thymus-derived CD8+ T cells. Most of the CD8α+ cells express CD11c and can be found in β2m/RAG-2 double-deficient mice, demonstrating that these cells do not require r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
5
0

Year Published

2001
2001
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 38 publications
2
5
0
Order By: Relevance
“…Different rules applied to memory H-Y TCR transgenic T cells, which required expression of class I MHC to survive and proliferate but did not distinguish the presence of cognate or noncognate class I (5). Similar conclusions have been drawn by other groups concerning a homeostatic interaction of CD4 and CD8 T cells with self class II and class I MHC molecules, respectively (6)(7)(8)(9)(10)(11)(12)(13)(14). Those studies concluded that naïve T cells require TCR interactions with self to survive.…”
supporting
confidence: 85%
“…Different rules applied to memory H-Y TCR transgenic T cells, which required expression of class I MHC to survive and proliferate but did not distinguish the presence of cognate or noncognate class I (5). Similar conclusions have been drawn by other groups concerning a homeostatic interaction of CD4 and CD8 T cells with self class II and class I MHC molecules, respectively (6)(7)(8)(9)(10)(11)(12)(13)(14). Those studies concluded that naïve T cells require TCR interactions with self to survive.…”
supporting
confidence: 85%
“…This supports the existence of peripheral homeostasis (2,3,12,(30)(31)(32), because neither the rate nor the composition of thymic-exported cells varies in response to changes in the peripheral T cell pool (11,20). Theoretically, T cell numbers could be restricted by the finite availability of signals similar to those required for naïve CD4 (33)(34)(35), CD8 (18,36), and memory (see refs. 37 and 38 for reviews) T cell survival.…”
Section: Fig 5 (A)supporting
confidence: 55%
“…It has been recently reported that most of the CD8 ϩ cells in ␤ 2 -M Ϫ/Ϫ animals do not express CD8␤, but express high levels of CD11c and CD11b, suggesting that they may be of dendritic cell lineage (19). In addition, CD8␣␣ T cells have been shown to be CD44 high (20).…”
Section: Phenotype Of Cd8 ϩ T Cells From Mhc Class Ia-deficient Micementioning
confidence: 99%